Special aspects of historical momentum in Uryakhai region between Russian Emperor Nikolay II indorsed "Agree” and "Successful” in 1914 - Bicheldey, Kaadyr-ool A. (The New Research of Tuva, 2014)
Article presents the author’s presentation at International Science Conference devoted to 100th  jubilee "United Tuva in united Russia: history, modernity, futures” (July 3-4, 2014, Kyzyl). It enunciates the Tuvan and Russian governments’ efforts in establishing the jubilee date (2009-2011) and registers historical documents found and consolidated by the Russian Academy of Sciences that confirm the Russian protectorate over Tuva in 1914.
Keywords: Uriankhai region; Nikolay II; protectorate; Russian Empire; historical documents; jubilee